2022
DOI: 10.3390/su141610155
|View full text |Cite
|
Sign up to set email alerts
|

Study on Green Building Promotion Incentive Strategy Based on Evolutionary Game between Government and Construction Unit

Abstract: Green buildings are considered to be an effective way to save energy, reduce emissions, and protect the environment. As one of the main bodies of green building construction, the construction unit’s willingness to build seriously affects the promotion of green building. Therefore, based on the viewpoints of natural persons and bounded rationality, this study constructs an evolutionary game analysis model, analyzes the impact of local government subsidy policies on the application strategies of construction uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Stakeholders interact with each other through multiple rounds of strategy selection to achieve a stable state of strategy selection, which is the same as the characteristics of evolutionary game theory (EGT) ( 38 ). At present, EGT has been successfully applied to various economic and social issues, such as environmental governance ( 39 42 ), supply chain collaboration ( 43 , 44 ), green building development ( 45 , 46 ), online car-hailing platform regulations ( 47 49 ) and elderly service provision ( 50 , 51 ). Therefore, EGT is more suitable for us to study the regulation of “Internet + Community Elderly Care” services.…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
“…Stakeholders interact with each other through multiple rounds of strategy selection to achieve a stable state of strategy selection, which is the same as the characteristics of evolutionary game theory (EGT) ( 38 ). At present, EGT has been successfully applied to various economic and social issues, such as environmental governance ( 39 42 ), supply chain collaboration ( 43 , 44 ), green building development ( 45 , 46 ), online car-hailing platform regulations ( 47 49 ) and elderly service provision ( 50 , 51 ). Therefore, EGT is more suitable for us to study the regulation of “Internet + Community Elderly Care” services.…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
“…Bootstrapping may be used to acquire a coefficient's standard error, which is then used to determine statistical significance. The next phase, following the guidelines laid forth in [40], was using the bootstrapping technique to see whether a reflective indicator makes a significant contribution to the relevant construct. The observed t value may be calculated using the bootstrap standard error.…”
Section: Cross Loadingmentioning
confidence: 99%
“…Save energy and cut emissions [29] Green construction [30] Government dynamic reward and punishment policy [31][32][33] Construction waste recycling [34,35]…”
Section: Research Topics Dimensions Source Papersmentioning
confidence: 99%
“…Geng X [30] established an evolutionary game model among developers, contractors, and the government from the perspective of consumers' different green preferences, studied the optimal strategy of the green construction system in different situations, and put forward effective suggestions for each subject. Li X [31], based on the evolutionary game theory, analyzed the influence of a local government subsidy policy on the application strategy of the construction unit. The research showed that in the long run, government subsidies cannot improve the willingness of the construction unit to promote green buildings, so controlling the amount of subsidies and strengthening publicity is conducive to encouraging the construction unit to participate in the transformation and upgrading of the construction industry.…”
Section: The Application Of Evolutionary Game In the Green Buildingmentioning
confidence: 99%